Politics and Terrorism of Immanuel Kant‘s Radical Evil - Grigonis, Gintautas (Politologija, 2021)
This article analyzes Immanuel Kant’s concept of radical evil within the broader corpus of Kant’s practical works in order to ascertain whether suicidal terrorism can be interpreted using his philosophical framework. Said analysis establishes the dynamic between radical evil and other characteristics of Kantian human nature – unsocial-sociability and propensity towards humanity, whilst focusing on the political implications of said dynamic. When analyzed utilizing the established framework of politics of radical evil, suicidal terrorism reveals the extremities of human behavior as well as potential flaws of Kantian philosophy.